Transforming HRM in the Metaverse: Enhancing Employee Engagement and Collaboration in Phygital Workspaces - Rama Devi Seshapu; Sanjay Bhayani; Jayendrasinh Jadav; Podilapu Hanumantha Rao (Universitas Nahdlatul Ulama Surabaya, 2026)
This study examined how immersive metaverse workspaces relate to employee engagement and performance in phygital work settings. A cross-sectional online survey produced 175 usable responses from employees and HR professionals aged 18–35 who had experience with Roblox, Decentraland, or Meta Horizon. The proposed model was assessed using confirmatory factor analysis and structural equation modeling. Immersive metaverse workspaces were positively associated with employee engagement (β = 0.59, p < 0.001), while avatar realism and social presence were positively associated with perceived employee performance (β = 0.47, p < 0.01). Experiential HR elements—augmented reality, NFT-based recognition, and sensory design—strengthened the relationship between immersive workspaces and engagement (interaction β = 0.33, p < 0.05). The study contributes by defining phygital HRM as the coordinated design of physical and immersive digital work experiences and by testing a role-consistent model grounded in employee engagement, social presence, media richness, and job resources. The findings suggest that HR managers should evaluate immersive tools as work-design resources while also addressing accessibility, privacy, digital fatigue, and ethical avatar use. Because the data were cross-sectional and self-reported, the results indicate associations rather than causal effects.